The Relationship Between Stature and Live Weight of Dairy Cows Between Birth and Maturity - Gibson MJ; Sneddon NW; Rogers CW; Back PJ; Dittmer KE; Martín NP (MDPI (Base, Switzerland), 2025)
Lactational and reproductive performance are strongly associated with cow live weight and capacity. However, there are limited data published describing capacity (thoracic) growth and the prediction of final stature and capacity from measurements at birth. Therefore, the aim of this study was to examine the relationship between stature and live weight of female dairy cattle between birth and maturity. Forty dairy cows, with records of stature and capacity from birth up until two years of age, underwent follow-up measurements for live weight, height at withers, wither-rump length, girth circumference and leg length on four occasions between 42 and 52 months of age. Measures of wither height, leg length and wither rump length at fourth mating had the strongest association with measures at birth (R2 > 0.90) compared to girth and live weight (R2 = 0.88 and 0.82, respectively). The weaker association between birth and maturity measures for girth is likely a reflection of the stronger relationship with live weight resulting in a later maturity (approximately 810 days) compared to linear measures such as height (approximately 730 days). Therefore, to maximise capacity, adequate nutrition is required until approximately 810 days of age when capacity growth is most sensitive to environmental input.
Keywords: bone; girth; height; nutrition; growth; mature size